Perkembangan Historis Tafsir 'Ilmi: Dari Tafsir Ilmiah Klasik hingga Interpretasi Saintifik Kontemporer - Safina Huljannah Hamdeh (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2026)
Scientific exegesis (tafsir 'ilmi) has become one of the most debated approaches in Qur'anic interpretation due to its attempt to correlate Qur'anic verses with scientific knowledge. While this interpretive trend has attracted considerable scholarly attention, existing studies have predominantly examined individual exegetes, methodological issues, or the compatibility between the Qur'an and modern science, leaving the historical evolution of tafsir 'ilmi across different intellectual periods insufficiently explored. This study aims to examine the historical development of tafsir 'ilmi from the classical period to the contemporary era while identifying the epistemological shifts that have shaped its interpretive paradigm. Employing a qualitative library research approach with historical and philosophical perspectives, this study analyzes primary and secondary sources on the history of Qur'anic exegesis and scientific interpretation. The findings reveal that the development of tafsir 'ilmi has undergone four major phases. During the classical period, scientific reasoning functioned primarily to reinforce theological arguments concerning divine creation. The medieval period witnessed a decline in scientific interpretation due to the dominance of sectarian and ideological tendencies. In the modern period, scientific exegesis re-emerged as a response to modernity and Western scientific advancement through figures such as Muhammad Abduh and Tantawi Jawhari. Subsequently, the contemporary period transformed tafsir 'ilmi into a more systematic and interdisciplinary approach, represented prominently by Zaghlul al-Najjar, while simultaneously generating enduring debates regarding the epistemological limits of integrating scientific theories into Qur'anic interpretation. This study contributes to the field of Qur'anic studies by offering a comprehensive historical framework that explains the evolution of scientific exegesis and clarifies the changing relationship between revelation, reason, and scientific knowledge across different periods of Islamic intellectual history.